Still star-crossed - Taub, Melinda (New York : Delacorte Press, 2013)
"After the deaths of Romeo and Juliet, mysterious figures in Verona are determined to reignite the feud between the Montagues and Capulets, so, for the sake of peace, the Prince orders Romeo's best friend Benvolio to marry Juliet's cousin Rosaline"--
Keywords: Benvolio -- (Fictitious character from Shakespeare) -- Juvenile fiction; Families -- Juvenile fiction; Vendetta -- Juvenile fiction; Romance fiction; Verona (Italy) -- History -- 16th century -- Juvenile fiction; Italy -- History -- 1559-1789 -- Juvenile fiction; Characters in literature -- Fiction; Families -- Fiction; Vendetta -- Fiction; Love -- Fiction; Verona (Italy) -- History -- 16th century -- Fiction; Italy -- History -- 1559-1789 -- Fiction; Romance fiction; Historical fiction; Young adult fiction; Romance fiction; Historical fiction